Analisis Pengaruh Penghindaran Pajak dan Faktor Lainnya terhadap Nilai Perusahaan - Tjenyani, Michella (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research was conducted with the aim to obtain empirical evidence on the effect of company size, company age, capital structure, financial performance, profitability, capital intensity, and tax avoidance on firm value. This research was conducted on all consumer non-cyclicals and consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period. The method used in sampling was purposive sampling. The sample obtained was 201 data from 67 companies. Hypothesis testing in this study used multiple regression analysis. The results of this research showed that company size, financial performance, and profitability affect firm value. Meanwhile, company age, capital structure, capital intensity, and tax avoidance had no effect on firm value.